Iodized salt induced thyrotoxicosis: Bangladesh perspective - Parveen, Shahanaz; Latif, SA; Kamal, MM; Asaduzzaman, M; Akther, A; Laila, ZH (Mymensingh Medical Journal, 2009)
Mymensingh Med J. 2009 Jul;18(2):165-8. The abstract of this article is available on the PubMed website